The Urgency of Enacting the Asset Confiscation Bill for the Eradication of Corruption and Money Laundering in Indonesia - Maulidah, Khilmatin; Sari, Ratna Kumala; Melissa, Aldisa; Fitryantica, Agnes (Universitas Islam Indonesia, 2025)
Corruption and money laundering are classified as extraordinary crimes due to their significant impact on state finances and their potential to destabilize the national economy. These crimes not only result in the direct loss of public funds but also undermine trust in state institutions, obstruct development programs, and damage Indonesia's international reputation. Given the magnitude of these threats, there is an urgent need for effective legal mechanisms to recover stolen assets swiftly and efficiently. This study explores the urgency of ratifying the Asset Confiscation Bill as a critical step in enhancing Indonesia’s legal framework for combating corruption and money laundering. Currently, Indonesia’s asset recovery mechanisms are limited by procedural constraints embedded in existing laws on corruption and money laundering. These laws generally require a court decision with permanent legal force before any assets can be confiscated. Such a requirement often hampers swift action and allows perpetrators to conceal or transfer illicit assets during lengthy legal processes. This study, which uses a normative legal research method, relies on an analysis of laws, legal doctrines, relevant literature, and legal dictionaries to assess the shortcomings of current asset confiscation regulations. The findings suggest that the Asset Confiscation Bill holds great potential to fill these legal gaps. If enacted, the bill could provide a legal basis for the non-conviction-based confiscation of assets, enabling law enforcement to act more decisively in reclaiming assets suspected to be linked to corruption or money laundering. Such a reform would significantly bolster Indonesia’s efforts to combat economic crimes and protect national financial integrity.